Karta zaliva Kovdy po opisi Otdi︠e︡lʹnoĭ Sʺemki Bi︠e︡lago mori︠a︡ 1891 g. / Kopirovalʺ khimicheskoi︠u︡ tushʹi︠u︡ N. Ali︠u︡shkevich. Korrektirovalʺ Podpolkovnikʺ M. Klykovʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1891)
Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; Title translation: Map of Kovda Bay, according to the independent survey of the White Sea in 1891.; Translation of margin title: White Sea, Kandalaksha Bay.; Greenwich meridian.; "Masshtabʺ 250 sazh. vʺ di︠u︡ĭmi︠e︡" = Scale 250 fathoms in inch.; "No. 262" -- bottom left margin Grayscale; 1:1,000,000